Hubungan Peran Kader Dengan Pelaksanaan Kegiatan Posyandu Lansia - Rusdi Rusdi; Eko Rianto; Devy Puspita (ITKES Wiyata Husada Samarinda, 2017)
To realize the development program of government policy through health services for the elderly in the elderly posyandu, activities in an effort to provide excellent health services, the role of cadres is very much needed in the elderly posyandu activities. Elderly Posyandu cadres prepare the implementation of posyandu, mobilize the community to attend and participate in posyandu activities, and assist health workers in registration, counseling, and various other public health businesses. The purpose of this study was to determine the relationship of the role of cadres with the implementation of elderly posyandu activities in the work area of ​​Samarinda Wonorejo Health Center. The method used in this study was descriptive analytic, and used a cross sectional design. The sampling technique used by Non Probability Sampling with a sample of 20 respondents data was collected using a questionnaire and observation sheet. The results of the Fisher exact test showed that the Significant value (Sig) of the Fisher Exact Test was 0.037 <α (0.05). So that Ha is accepted which means that there is a relationship between the role of cadres of the elderly posyandu activities and the implementation of the Elderly Posyandu activities in the Wonorejo Samarinda Community Health Center. The role of cadres is related to the elderly posyandu activities. Puskesmas are expected to provide special training for cadres to improve their roles and duties in the implementation of elderly posyandu activities.